Knowledge and Adoption of Bt Cotton Cultivation Practices - Rajput, H. D.; Chinchmalatpure, Umesh R. (Indian Journal of Extension Education, 2016)
The present study was conducted in Jalgaon and Dhule district of North Maharashtra, with a random sample of 175 Bt  cotton growers, to measure the level of knowledge of Bt cotton growers and to understand the relationship between  selected characteristics of Bt cotton growers and their extent of adoption. The results indicate that majority of the  respondents had medium (53.71 per cent) level of adoption towards cultivation practices of Bt cotton. The analysis of  correlation revealed that variables viz., education, area under Bt cotton, annual income, socio-economic status, social  participation, scientific orientation, cosmopoliteness, extension contact and knowledge had positive and significant  influence on their level of knowledge.
Keywords: Adoption; bt cotton; cultivation practices; bacillus thuringiensis (bt)